A novel simulation of bellman-dymo protocol in vanet’s ad-hoc network - Pavithra, L; Sivakumar, V; Anuja, S (International Journal of Engineering and Technology, 2018)
Vehicular Ad-hoc Networks (VANET’s) is the recent technology to facilitate the study of simulators. The mobility model and physical layer are the issues in the simulator which impact the output greatly. The simulations of the routing algorithm in the VANET’s are still the major problem. The comparison between the routing protocols is addressed by only some few works. In order to overcome these issues and problems we made a comparison between the hybrids, reactive, geographic routing and pro-active routing protocols by using a simulation platform by integrating the mobility and the physical layer models. It also performs a comparison between the multi-path routing protocols with Ad-hoc network which allows adapting the faster performance. By using the BDYMO protocol in the VANET communication, the overhead in the network is minimized and the performance is improved.